Correlation of Blood Cholesterol Levels and Hypertension with The Incidence of Stroke in The Provincial Hospital of Banjarmasin - Muhammad Saputra; Candra Kusuma Negara; Anna Martiana Afida; Henny Puspasari; Akhmad Murjani (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2019)
Introduction: Stroke risk factors are related to the circumstances of a person's health status, namely hypercholesterolemia (excess cholesterol levels) and hypertension (high blood pressure).Methods: A correlative descriptive analytic observational study using cross sectional approach. The number of samples taken is as many as 62 people using the Slovinformula..Statistical analysis uses Sperman Rank Test and Linear regression test.Results: The results of this study indicate that the total cholesterol level of patients from 62 samples found that normal cholesterol levels amounted to 29 people (46.8%) consisting of 12 people (19.4%) with SH and 17 people ( 27.4%) with SNH and high cholesterol levels totaling 33 people (53.2%) divided into 7 people (11.3%) with SH and 26 people (42%) with SNH. There is a significant correlation between blood cholesterol levels with stroke incidence in statistical tests with p value 0,004 (p<0,05), there is a significant correlation between hypertension and stroke events withp value 0,031(p<0,05)there is no significant correlation between blood cholesterol levels and hypertension in statistical tests withp value 0,129 (p>0,05) and by using Linear regression test obtained that the correlation between blood cholesterol levels with a value of mean value hypertension  0.453 and mean 0.994 so that the most dominant with the incidence of stroke was hypertension.Conclusions: Have nothing to do with hypertension, it can be concluded here that stroke is caused by hypertension. The Suggestion is hypertension’s not only caused by cholesterol levels but there are other triggers that cause it.